A TIMS-TOF mass spectrometry study of disaccharides from in situ ESI derivatization with 3-pyridinylboronate. Issue 1 (7th December 2020) - Li, Lei; Yu, Jiancheng; Xie, Chengyi; Wang, Chenlu; Guan, Pengfei; Hu, Jun Jack; Tang, Keqi
Abstract : Mobilograms of in situ ESI 3-pyridinylboronic acid tagging of isomaltose in the positive or negative mode. Abstract : 3-Pyridinylboronate, a zwitterionic boronic acid, displayed effective in situ ESI for reversible covalent tagging of saccharides in both cation and anion modes. The ion mobilities of thus-generated ions were examined with the Bruker timsTOF fleX instrument. Nine disaccharides were examined using this method. They have identical mass-to-charge ratios, differing only in monomer compositions, regio-linkages, and anomeric configurations (α or β). The IMS separations of the disaccharides from this method were compared with those from sodium adducts reported in the literature. The differentiation effects of this method on the disaccharide isomers were increased on average by an order of magnitude. Using this method, all the pairs of disaccharides selected from nine isomers were completely identified by comparing the mobility spectra of single-tagged and double-tagged ions.